Behavior Setting Pemanfaatan Tanah Ulayat dalam Pola Penataan Ruang Waris dan Sirkulasi Kawasan Studi Kasus Korong Tarok Nagari Kepala Hilalang - Asri Mariza Oktavia; Suparwoko (Retii, 2019)
Abstract. Behavior setting is the user's behavior towards the environment in forming spaces according to activities. With the development and population growth problems arise in the use of land, especially customary land. The issue of unclear structuring patterns, applicable legal dualism, and control of land from communal land belonging to a people becomes SHM that occurs in overseas areas. Overseas area is the development area of ​​the original Minangkabau luhak region. Where customary law has been combined with state law. Departing from these issues the question arises how the behavior setting in the process of obtaining inheritance land related to the layout of land and buildings and circulation paths obtained. Primary and secondary data is obtained through drawing, photographing, writing, interviewing, and obtaining documents related to the Minangkabau customary inheritance process. Supporting data obtained through the study of literature and regulations - regulations. Analysis is carried out using a behavior setting approach through user studies, activities and needs to obtain a typology of spatial use patterns that produce a place center mapping. To obtain the pattern of arrangement, history or phenomenology of inheritance and use of traditional land. Data analysis was supported by triangulation through traditional figures, indigenous peoples' speakers and literature related to behavior settings. The results obtained that there are three typologies of users in the utilization of inheritance land inheritance, namely the inheritance of the family inheritance space on the side of the road, the inheritance typology behind the family inheritance space, and the inheritance typology of migrant inheritance space behind the inheritance space. Keywords: behavior setting, customary law, inheritance space pattern, ulayat land